2023
DOI: 10.1002/jsfa.12418
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the aroma profile of quinoa (Chenopodium quinoa Willd.) and assessment of the impact of malting on the odor‐active volatile composition

Abstract: Background: Quinoa (Chenopodium quinoa Willd.) is a gluten-free pseudocereal, rich in starch and high-quality proteins. It can be used as a cereal. Recently, a variety of nontraditional food products were developed; however, the sharp bitterness and the earthy aroma of unprocessed quinoa interfered with the acceptance of these products. Malting of cereals is known to improve their processing properties and enhance their sensory quality. To evaluate the acceptance and potential of quinoa malt as a raw material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Pyrazine is mainly formed by the reaction between amino ketones ( Wei et al, 2020 ). It is reported that pyrazine is an important volatile compound for adding roasting flavor to foods ( Almaguer et al, 2023 ). 2,3-dimethyl pyrazine produces caramel, cocoa, peanut butter, and roasted aromas, playing an important role in quinoa aroma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyrazine is mainly formed by the reaction between amino ketones ( Wei et al, 2020 ). It is reported that pyrazine is an important volatile compound for adding roasting flavor to foods ( Almaguer et al, 2023 ). 2,3-dimethyl pyrazine produces caramel, cocoa, peanut butter, and roasted aromas, playing an important role in quinoa aroma.…”
Section: Resultsmentioning
confidence: 99%
“…2-mercaptoethanol and tetrahydrofurfuryl alcohol produce a typical nutty aroma, which were only detected in the RGQ samples. Esters contribute to the characteristic flavor of most grains, producing ester, floral, and fruit aromas ( Almaguer et al, 2023 ). Methyl isobutyrate (flower, fruit) and hexyl formate (fruit) were also only detected in the RGQ samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High and low concentrations are shown in black and white, respectively. Odor descriptions as perceived at the sniffing port are listed on the right (Almaguer et al., 2023). Rectangles on the left grouped compounds by chemical class; both furans and the lactone included in others.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike barley, all alcohols increased until the last day of germination in rye, except octan‐1‐ol. Similar to barley, 3‐methylbutan‐1‐ol, 2‐phenylethan‐1‐ol, hexan‐1‐ol, and ( E )‐hex‐2‐en‐1‐ol were the most abundant alcohols in germinating rye, these contribute green, grassy, and floral notes (Almaguer et al., 2023). In quinoa, all alcohols increased with germination, except ( E )‐hex‐2‐en‐1‐ol.…”
Section: Resultsmentioning
confidence: 99%